2010
DOI: 10.3233/jad-2010-100465
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Mitochondrial Reactive Oxygen Species Generation: How to Read the Facts

Abstract: Abstract. A number of recent discoveries indicate that abnormal Ca2+ signaling, oxidative stress, and mitochondrial dysfunction are involved in the neuronal damage in Alzheimer's disease. However, the literature on the interactions between these factors is controversial especially in the interpretation of the cause-effect relationship between mitochondrial damage induced by Ca 2+ overload and the production of reactive oxygen species (ROS). In this review, we survey the experimental observations on the Ca 2+ -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 168 publications
(164 reference statements)
2
143
0
Order By: Relevance
“…Within mitochondria, Ca 2+ uptake, transmembrane potential, and ROS generation are extensively interrelated (33,38,47). Mitochondrial Ca 2+ can stimulate OXPHOS, promoting ROS generation from respiratory complexes I and III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within mitochondria, Ca 2+ uptake, transmembrane potential, and ROS generation are extensively interrelated (33,38,47). Mitochondrial Ca 2+ can stimulate OXPHOS, promoting ROS generation from respiratory complexes I and III.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Ca 2+ can drive ROS production through stimulation of mitochondrial activity (33,38,39). We have previously shown that mitochondrial Ca 2+ is increased within dying cells following aminoglycoside exposure in a manner resembling mitochondrial Ca 2+ overload (36).…”
Section: Mitochondrial Ca 2+ Uptake Is Necessary For Mitochondrial Anmentioning
confidence: 99%
“…Even though the mechanism controlling the mitochondrial membrane potential ΔΨm in vivo are complex and not fully understood, 'mild un-coupling' of mitochondria are turned on in vivo to diminish the formation of ROS [38]. Decreased ΔΨm, due to the uncoupling of electron flow from ATP synthesis by increased proton permeability of the inner mitochondrial membrane, can reduce ROS production at complex I by decreasing NAD(P)H/NAD(P) + and possibly by decreasing the life span of the semiquinone radical [39]. Such decrease in the mitochondrial membrane potential (ΔΨm) primarily attenuates mitochondrial RO production with a consequential decrease in mitochondrial Ca 2+ uptake [40], preventing mitochondrial calcium overload and the a b c d e f Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such mismatches have been considered to promote superoxide anion generation. 173,175 This might be the reason for the strong expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha in PV þ interneurons, at least during certain stages of brain development. 176,177 Peroxisome proliferatoractivated receptor gamma coactivator 1-alpha has the capability to induce the expression of enzymes involved in glutathione biosynthesis as well as of ROS-detoxifying enzymes such as As a perspective, the functional consequences of metabolic stress in fast-spiking interneurons are illustrated.…”
Section: Perspective: Metabolic and Oxidative Stress In Fast-spikingmentioning
confidence: 99%